LEGAL ANALYSIS OF THE DIVISION OF JOINT PROPERTY ON LAND OWNED BY ONE PARTY'S PARENTS ACCORDING TO MARRIAGE LAW (STUDY OF DECISION NUMBER 183/Pdt.G/2025/MS.Sgi) - Rizki Ardita; Beby Sendy; Bambang Fitrianto (PT. Radja Intercontinental Publishing, 2025)
This study was conducted to analyze the division of joint assets and the judge's legal considerations in determining the status of joint assets standing on land owned by one of the parties' parents and the suitability of the decision with the provisions of Law Number 1 of 1974 concerning Marriage. The method used in this study is normative law with a case approach, namely analyzing secondary data in the form of the decision of the Mahkamah Syar’iyah Sigli Number 183 / Pdt.G / 2025 / MS.Sgi as well as laws and legal materials related to joint assets. This study shows that in this case, the object of the dispute is a permanent house unit standing on land owned by the Plaintiff's parents which is recognized as joint assets, while the land where the house stands is the Plaintiff's inherited property, but in its consideration the Panel of Judges did not clearly outline the boundaries between joint assets in the form of a house and land as inherited property, but instead immediately decided that the Defendant should divide 2 houses in kind. So that the decision can give rise to double interpretations as if the land where the house stands is also part of the joint assets. This creates legal uncertainty in the implementation of the decision and could potentially harm one of the parties. Therefore, the division of joint assets should be carried out fairly by clearly separating the house as joint property from the land as acquired property, in order to comply with the provisions of the Marriage Law.